Antimicrobial Resistance and Cytotoxicity of Citrobacter spp. in Maanshan Anhui Province, China - Liyun Liu; Liyun Liu; Ruiting Lan; Liqin Liu; Yonglu Wang; Yushi Zhang; Yiting Wang; Yiting Wang; Jianguo Xu; Jianguo Xu (Frontiers in Microbiology, 2017)
Objectives:Citrobacter spp. especially Citrobacter freundii, is frequently causing nosocomial infections, and increasingly becoming multi-drug resistant (MDR). In this study, we aimed to determine the genetic diversity and relationships of Citrobacter spp. from diarrheal patients and food sources, their antimicrobial resistance profiles and in vitro virulence properties.Methods: Sixty two Citrobacter isolates, including 13 C. freundii, 41 C. youngae and eight C. braakii isolates, were obtained from human diarrheal patients and food sources. Multilocus Sequence Typing (MLST) of seven housekeeping genes and antimicrobial susceptibility testing using the broth microdilution method according to CLSI recommendations were carried out. Adhesion and cytotoxicity to HEp-2 cells were performed. PCR and sequencing were used to identify blaCTX−M, blaSHV, blaTEM and qnr genes.Results: The 62 isolates were divided into 53 sequence types (STs) with all STs being novel, displaying high genetic diversity. ST39 was a predominant ST shared by 5 C. youngae strains isolated from four foods and a diarrheal patient. All isolates were resistant to cefoxitin, and sensitive to imipenem, meropenem and amikacin. The majority of Citrobacter isolates (61.3%) were MDR of three or more antibiotics out of the 22 antibiotics tested. Two C. freundii isolates each carried the blaTEM−1 gene and a variant of qnrB77. Three Citrobacter isolates each carried qnrS1 and aac(6')-Ib-cr genes. Seven isolates that showed strong cytotoxicity to HEp-2 cells were MDR.Conclusions:Citrobacter spp. from human and food sources are diverse with variation in virulence properties and antibiotic resistance profiles. Food may be an important source of Citrobacter species in transmission to humans. C. freundii and C. youngae are potential foodborne pathogens.